Akibat Hukum Penetapan Tersangka Terhadap Orang Mati Dalam Proses Penyidikan - Serlaloy, Alfred Gilbert; Toule, Elsa Rina Maya; Salamor, Anna Maria (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The research in this thesis is motivated by the determination of suspects regarding dead people. In Article 109 paragraph (2) of the Criminal Procedure Code, investigators must pay attention to the provisions regarding disclosure of investigations if the suspect dies. Legally, Article 77 of the Criminal Code states